1995
DOI: 10.1017/s003329170003347x
|View full text |Cite
|
Sign up to set email alerts
|

Lateralized abnormality of high energy phosphate metabolism in the frontal lobes of patients with bipolar disorder detected by phase-encoded31P-MRS

Abstract: SYNOPSISHigh energy phosphate metabolites were measured using phase-encoded in vivo phosphorus-31 magnetic resonance spectroscopy (31P-MRS) in both the left and right frontal lobes of 25 patients with bipolar disorder. Eleven patients were examined in the depressive state, 12 in the manic state, and 21 in the euthymic state. Twenty-one age-matched normal volunteers were also examined. The phosphocreatine (PCr) peak area percentage in the left frontal lobe in the patients in the depressive state was decreased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
85
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(92 citation statements)
references
References 34 publications
5
85
1
1
Order By: Relevance
“…[4] we see that gain is largest when T 1 Ͼ TR. Additionally, by setting dGain/d␣ ϭ 0 and solving for ␣, we find that gain is maximized when …”
Section: Lfa Methodsmentioning
confidence: 68%
See 1 more Smart Citation
“…[4] we see that gain is largest when T 1 Ͼ TR. Additionally, by setting dGain/d␣ ϭ 0 and solving for ␣, we find that gain is maximized when …”
Section: Lfa Methodsmentioning
confidence: 68%
“…Since studies at 1.5T and 2T have shown that bipolar subjects have decreased membrane phospholipid precursor levels in their temporal (2) and frontal lobes (3), and a deficit of high-energy phosphates in their frontal lobes (4), as compared to normal subjects, the development of a quantitative technique that evaluates these particular metabolites is crucial for diagnosis. However, 31 P MR spectroscopy (MRS) quantitative techniques are confounded by low signal-to-noise ratio (SNR) and poor spatial resolution.…”
mentioning
confidence: 99%
“…31 Together, these studies add neurochemical support to the contention that mood disorders are associated with regional neuronal loss and/or reductions in neuronal viability/function. There have also been a number of reports of abnormal brain high energy phosphate metabolism in mood disorder patients, most notably decreased phosphocreatine (PCr) and/or ATP levels, [32][33][34][35][36][37][38] as well as abnormal phospholipid metabolism (predominantly phosphomonoesters and phosphodiesters). 33,34,36,37,39,40 The most extensive series of studies investigating possible abnormalities in brain energy regulation in mood disorders have been conducted by Kato and associates.…”
Section: Volumetric Brain Imagingmentioning
confidence: 99%
“…Most information about PI metabolism in BPD derives from studies using tissues other than CNS (Atack et al 1995;Feldman et al 1997). Indirect evidence for altered PI metabolism in individuals with BPD has been suggested by a reduction in cytosolic and membrane-associated PKC activities in platelets of lithium-treated subjects with BPD (Friedman et al 1993); and by elevated platelet membrane phosphatidylinositol-4,5-bisphosphate (PIP2) in medication-free patients with BPD during the manic phase (Brown et al 1993).Indirect in vivo measurement of brain inositol metabolism in adult patients treated with lithium has been attempted through measuring phosphomonoester peaks with phosphorus ( 31 P) magnetic resonance spectroscopy (MRS) (Kato et al 1995), proton ( 1 H) MRS (Kato et al 1996;Silverstone et al 1996) and lithium MRS (Gonzalez et al 1993;Kato et al 1993;Sachs et al 1995) (involving a lithium-sensitive coil). In vivo 1 H MRS is a non-invasive technique for measuring metabolite concentrations in living tissue .…”
mentioning
confidence: 99%
“…Indirect in vivo measurement of brain inositol metabolism in adult patients treated with lithium has been attempted through measuring phosphomonoester peaks with phosphorus ( 31 P) magnetic resonance spectroscopy (MRS) (Kato et al 1995), proton ( 1 H) MRS (Kato et al 1996;Silverstone et al 1996) and lithium MRS (Gonzalez et al 1993;Kato et al 1993;Sachs et al 1995) (involving a lithium-sensitive coil). In vivo 1 H MRS is a non-invasive technique for measuring metabolite concentrations in living tissue .…”
mentioning
confidence: 99%